Selection of suitable media and intervals of media inoculation for culturing Tubificid worms (Journal of the Bangladesh Agricultural University, 2013)
Tubificid worms are aquatic invertebrates, belonging to the class Oligochaeta and family Tubificidae, used as an important live food for fishes. The study was conducted to culture Tubificid worms under running water in order to develop a suitable culture media and an optimum duration of media inoculation for culturing Tubificid worms. The worms were cultured under two experiments in cemented culvert system (160×25×10 cm3) for 90 days. In the first experiment the worms were cultured in three different media designated as treatment-I, treatment-II and treatment-III. The highest yield (503.39±22.98 mg cm-2) was found at 70th day of culture duration in the culture media containing a mixture of 35% mustard oil cake, 20% wheat bran, 25% cow-dung and 20% fine sand (treatment-III). Only 1.99 kg media ingredients valued BDT 29.85 were needed to yield 1 kg worms. In the second experiment, the worms were cultured at three different intervals of media inoculation i.e., 6, 10 and 15 days interval designated as treatment-I, treatment-II and treatment-III respectively using the media found best in the first experiment. Inoculation of media at 10 days interval showed significantly (P